2009
DOI: 10.1152/jn.90893.2008
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Eye Cortical Maps Are Uniquely Sensitive to Binocular Plasticity

Abstract: Faguet J, Maranhao B, Smith SL, Trachtenberg JT. Ipsilateral eye cortical maps are uniquely sensitive to binocular plasticity. J Neurophysiol 101: 855-861, 2009. First published December 3, 2008 doi:10.1152/jn.90893.2008. In the cerebral cortex, neuronal circuits are first laid down by intrinsic mechanisms and then refined by experience. In the canonical model, this refinement is driven by activity-dependent competition between inputs for some limited cortical resource. Here we examine this idea in the mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…To model MD, in which the visual stimulus reaches the contralateral eye only after penetration through the closed eyelid, we assume the visual component of the closed-eye is blurred (Faguet et al, 2009) and weakened by half. Such blurring is known to influence V1 development (White et al, 2001; Akerman et al, 2002), and has been suggested to underlie the slowing of retinotopic development by MD but not monocular inactivation (MI) during the pre-CP (Smith and Trachtenberg, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To model MD, in which the visual stimulus reaches the contralateral eye only after penetration through the closed eyelid, we assume the visual component of the closed-eye is blurred (Faguet et al, 2009) and weakened by half. Such blurring is known to influence V1 development (White et al, 2001; Akerman et al, 2002), and has been suggested to underlie the slowing of retinotopic development by MD but not monocular inactivation (MI) during the pre-CP (Smith and Trachtenberg, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…2C). The refinement decreased due to the broadly correlated residual visual stimulus through the deprived eyelid (Faguet et al, 2009). Despite a dramatic change in the distance over which visual inputs were correlated, the RF widened only by about 30% (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, loss of responsiveness occurs also during complete visual deprivations (Wiesel and Hubel, 1965;Freeman et al, 1981;Kaneko et al, 2008;Faguet et al, 2009;Iurilli et al, 2011). In addition, depression of closedeye responses and potentiation of openeye responses are two temporally (Mioche and Singer, 1989;Frenkel and Bear, 2004) and mechanistically (Heynen et al, 2003;Kaneko et al, 2008) distinct processes that can occur independently (Yoon et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…33 Contralateral eye enucleation in mice accelerates the improvement of retinotopic organization (cortical refinement) and increases responsive area in V1 (cortical reorganization). 16,34 Compared with eyelid suture, postnatal ME greatly reduces ocular dominance columns associated with the enucleated eye in monkeys. 35 Prenatal ME obliterates LGN layer segregation and ocular dominance in area V1 of monkeys.…”
mentioning
confidence: 99%